Yield, Suitability and Sensory Evaluation of Gari Produced from Two Cassava Varieties at Different Age - Adeyemi Gbolagade Adegbola; Muhammed Dauda; Adenike Rahmatallah Alawode; Ogbori Bernard Odey (International Journal of Natural Sciences: Current and Future Research Trends, 2020)
The age at which some cassava roots are harvested can affect the yield and it’s suitability of gari prepared from them. Two improved cassava varieties, TME 419 and TMS 30572 were investigated in this study. They were planted in April and harvested in the following year at the ages of 9, 12 and 15 months. 10kg of each fresh cassava varieties at different ages were weighed and processed into gari. The effects of age at harvest on selected cassava varieties on yield and suitable of gari were studied. Some investigated parameters on gari includes: percentage yield (Y), moisture content (MC), swelling index (SI) and sensory evaluation (SE). Results showed that gari yield (Y) % of the TME 419, 9, 12 and 15 months were 27%; 35% and 35% while TMS 30572, 9, 12 and 15 months were 21%; 39% and 52% respectively. (MC) of TME 419, 9, 12 and 15 months were 3.3; 5.3 and 2.6 while TMS 30572, 9, 12 and 15 months were 3.1; 3.4 and 4.8 respectively. (SI) showed that TME 419, 9, 12 and 15 months were 2.92; 2.96 and 3.0 while TMS 30572, 9, 12 and 15 months were 3.02; 3.0 and 3.2. Sensory analysis results indicated that almost all the samples were highly rated, however, TMS 30572 and TME 419 of 9 months were dislike in terms of taste. The study has shown that the age at which some cassava roots are harvested can affect the yield and the suitability of gari prepared from them. There was varietal effect on the yield and suitable of the two varieties. It can be concluded from the study that cassava age 12 months and 15 months of both varieties were suitable for gari than their 9 months.